Microbial Fabrication of Zinc Oxide Nanoparticles and Evaluation of Their Antimicrobial and Photocatalytic Properties - Jain, Devendra; Shivani,; Bhojiya, Ali Asger; Singh, Himmat; Daima, Hemant Kumar; Singh, Mandeep; Mohanty, Santosh Ranjan; Stephen, Bjorn John; Singh, Abhijeet (Frontiers in Chemistry, 2020)
Zinc oxide (ZnO) nanoparticles have attracted significant interest due to their vast applications. However, green synthesis of ZnO nanoparticles is a challenge, and therefore, here we report zinc tolerant bacteria assisted microbial synthesis of ZnO nanoparticles. Furthermore, the effective antimicrobial potential and photocatalytic dye degradation capabilities of these nanoparticles are also evaluated. The ZnO nanoparticles are characterized using a range of physicochemical characterization techniques confirming nanoscale size, uniformspherical shape, and high negative surface charge. The ZnO nanoparticles showed considerable antibacterial and antifungal activities. Further, the photocatalytic degradation of methyl orange under UV lamp was studied and results reveal that ZnO nanoparticles have good photocatalytic potential as well.